2021
DOI: 10.1038/s41368-021-00123-7
|View full text |Cite
|
Sign up to set email alerts
|

PER2-mediated ameloblast differentiation via PPARγ/AKT1/β-catenin axis

Abstract: Circadian rhythm is involved in the development and diseases of many tissues. However, as an essential environmental regulating factor, its effect on amelogenesis has not been fully elucidated. The present study aims to investigate the correlation between circadian rhythm and ameloblast differentiation and to explore the mechanism by which circadian genes regulate ameloblast differentiation. Circadian disruption models were constructed in mice for in vivo experiments. An ameloblast-lineage cell (ALC) line was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…A similar oscillation was observed in p75NTR and Runx2 mRNA expression but not in Dlx1 mRNA expression, indicating that p75NTR and mineralizationrelated factor Runx2 might be involved in the circadian rhythm of tooth development. Previous studies support this finding that clock genes (Bmal1, Clock, Per1, and Per2) and two markers of ameloblast differentiation (amelogenin and kallikrein-related peptidase 4) have regular oscillations in ameloblasts (Zheng et al, 2013;Huang et al, 2021). Moreover, this oscillation was affected by L.D.…”
Section: Figurementioning
confidence: 54%
See 1 more Smart Citation
“…A similar oscillation was observed in p75NTR and Runx2 mRNA expression but not in Dlx1 mRNA expression, indicating that p75NTR and mineralizationrelated factor Runx2 might be involved in the circadian rhythm of tooth development. Previous studies support this finding that clock genes (Bmal1, Clock, Per1, and Per2) and two markers of ameloblast differentiation (amelogenin and kallikrein-related peptidase 4) have regular oscillations in ameloblasts (Zheng et al, 2013;Huang et al, 2021). Moreover, this oscillation was affected by L.D.…”
Section: Figurementioning
confidence: 54%
“…Previous studies reported the detection of clock genes in dental germs and depicted a regular oscillation expression pattern, indicating that biological clocks affect tooth development (Nirvani et al, 2017;Papakyrikos et al, 2020;Huang et al, 2021). The 48-h circadian rhythm dynamics in rat EMSCs showed that the clock genes Bmal1, Clock, and Per1 presented a regular oscillation in mRNA expression.…”
Section: Figurementioning
confidence: 86%
“…Mutations in KLK4 could cause nonsyndromic enamel malformations in humans and mice ( Lu et al, 2008 ). The expression of AMELX and PPARγ was decreased in Per2 knockdown ameloblast lineage cells, and overexpression of PPARγ partially reversed this phenomenon, Per2 regulates ameloblast differentiation mainly via the PPARγ/AKT1/β-catenin signaling axis ( Huang et al, 2021 ). Runx2 is involved in the whole process of tooth development, and Runx2 knockout mice are a representative congenital tooth agenesis model ( Chen et al, 2020 ).…”
Section: Circadian Rhythm/clock Genes Regulate Maxillofacial Embryoni...mentioning
confidence: 99%
“…Mechanistically, circadian rhythm alterations have been linked to the ß-catenin/WNT-signaling pathway. Indeed, circadian rhythm disrupted mice were demonstrated to exhibit both a decrease in expression of Bmal1 and β-catenin [ 23 ]. Bmal1, the major regulator of circadian activity, was shown to stimulate the WNT/β-catenin pathway by enhancing the transcription of β-catenin, decreasing the degradation of β-catenin [ 24 ], and downregulating Glycogen synthase kinase-3β (GSK-3β) activity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%